Migração do ensino presencial para o emergencial remoto : uma experiência no ensino da língua inglesa - Feijó, Jéssica Azambuja (2021)
Because of the pandemic due to the new Coronavirus, COVID-19, everyone has been forced to leave the routine they were used to, having to learn to live in a different way. Among the various sectors of society that were impacted, and needed to provide an urgent response, there is the education area. Suddenly, it was necessary to migrate from face-to-face to remote teaching, and the challenge of this transposition implied emergency training processes. Teachers were confronted to the complexity of remote work, adopting digital platforms. The gap in the educational system's disparity was more exposed. The way of teaching and learning had to be adapted and, along with it, it appeared the insecurity and uncertainty as to whether students would remain as engaged as they were in face-to-face teaching. This research had the objective to describe and to analyze aspects involved in the emergency migration of the first semester of 2020, in a franchised language school, located in the city of Gravataí, Rio Grande do Sul. The investigation was based by a literature review and interviews with seven teachers to tell about their experiences and impressions about the migration process from face-to-face classes to remote classes. As a contribution, it stands out the planning process, the difficulties faced, the solutions constructed and how the teachers adapted methodologies to be able to maintain the engagement and service of the students, considering that this specific training (second language) is a family decision that had to be re-signified in times of so many demands and diverse restrictions.